2023
DOI: 10.1111/nph.19263
|View full text |Cite
|
Sign up to set email alerts
|

Microbe‐dependent and independent nitrogen and phosphate acquisition and regulation in plants

Boyu Zhao,
Xianqing Jia,
Nan Yu
et al.

Abstract: SummaryNitrogen (N) and phosphorus (P) are the most important macronutrients required for plant growth and development. To cope with the limited and uneven distribution of N and P in complicated soil environments, plants have evolved intricate molecular strategies to improve nutrient acquisition that involve adaptive root development, production of root exudates, and the assistance of microbes. Recently, great advances have been made in understanding the regulation of N and P uptake and utilization and how pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 153 publications
0
10
0
Order By: Relevance
“…Carbon, nitrogen, and phosphorus are essential elements in plants, playing different ecological roles in the natural environment, and there is also a close correlation between them; Moreover, the nitrogen and phosphorus contents of plants have a certain effect on the production capacity and carbon fixation of terrestrial ecosystems ( Tang et al., 2018 ). This is because nitrogen can promote the absorption of radioactive carbon in plants and promote the metabolic activity of plant growth ( Kopittke et al., 2016 ); The interrelationship between nitrogen and phosphorus is very close ( Zhao et al., 2023 ), and the N: P value of plant leaves can be used to determine the nutrient constraints on their growth and development ( Wang et al., 2013 ; Mao et al., 2016 ). This study found that under different rainfall patterns, there was a significant positive correlation between carbon-nitrogen, carbon phosphorus, and nitrogen phosphorus in the same organ ( P <0.05), and the majority of the curve fit R 2 was above 0.75, with the highest fit reaching 0.971 ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Carbon, nitrogen, and phosphorus are essential elements in plants, playing different ecological roles in the natural environment, and there is also a close correlation between them; Moreover, the nitrogen and phosphorus contents of plants have a certain effect on the production capacity and carbon fixation of terrestrial ecosystems ( Tang et al., 2018 ). This is because nitrogen can promote the absorption of radioactive carbon in plants and promote the metabolic activity of plant growth ( Kopittke et al., 2016 ); The interrelationship between nitrogen and phosphorus is very close ( Zhao et al., 2023 ), and the N: P value of plant leaves can be used to determine the nutrient constraints on their growth and development ( Wang et al., 2013 ; Mao et al., 2016 ). This study found that under different rainfall patterns, there was a significant positive correlation between carbon-nitrogen, carbon phosphorus, and nitrogen phosphorus in the same organ ( P <0.05), and the majority of the curve fit R 2 was above 0.75, with the highest fit reaching 0.971 ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the higher soil organic matter content in alpine regions reflects, to some extent, a reduced resource utilization capacity [ 49 ]. With increased soil nitrogen and phosphorus contents, soil nutrient availability decreases significantly, prompting plants to allocate more resources to root systems for enhanced soil resource acquisition [ 50 ]. This increased root biomass allows plants to explore a larger soil volume for nutrient uptake, leading to higher BGBP levels [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of molecular, isotopic, and ecological approaches has continued to advance our understanding. Resource exchange between plants and fungal symbionts is crucial for nutrient cycling (Zhao et al ., 2024, in this issue pp. 1507–1522).…”
Section: Nutrient Cyclingmentioning
confidence: 95%